An Examination of Adults on Antipsychotic Medication at Risk for Metabolic Syndrome: A Comparison with Obese and Eating Disorder Populations. (31st August 2012) - Stiles‐Shields, Colleen; Bogue, Cynthia; Grange, Daniel Le; Yohanna, Daniel
Abstract Little research has explored how eating disorders (ED) may be involved in the increased risk for metabolic syndrome in adults on antipsychotic medication. This pilot study compared participants on antipsychotic medication with obese and ED samples with respect to demographic and psychosocial factors. Participants (antipsychotic medication n = 12; obese n = 12; ED n = 12), were adults presenting to an outpatient psychiatry department (83.3% women; M age = 45.75 ± 11.5). Analysis of variance, analysis of covariance and chi‐square tests were used to compare the samples. Participants on antipsychotic medications had a significantly lower mean body mass index than the obese (p < .001) and ED (p < .05) samples, as well as significantly lower Restraint Total scores (p < .05) and subjective binge episode frequency (p < .05) than the ED sample. The lack of significant differences that occurred between the antipsychotic medication sample and two eating disorder samples significantly different from one another indicates that this population may have unique symptomology and treatment needs. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.